Fast well to get maximum benefits - Abd Razak, Dzulkifli (2007)
THIS is the time of the year when Muslims around the world indulge themselves in the obligatory fasting. It is primarily an act of abstaining from eating and drinking from dawn to dusk for the entire holy month of Ramadan. Fasting during the holy month of Ramadan, the ninth month of the Islamic calendar (Hijri calendar), is the fourth pillar of Islam. Fasting also forbids one from useless activities such idle talk or, worse still, slander and backbiting that could lead to anger, envy, greed and gossip, to name a few.